Simulasi Penghilangan Noise pada Sinyal Suara menggunakan Metode Fast Fourier Transfrom - Septiawan, Redza Dwi; Rayes, Putri Rahmasari; Robbaniyyah, Nuzla Af'idatur (Semeton Mathematics Journal, 2024)
Sound signals are widely used such as when communicating, recording, or medical testing. However, voice signals are often contaminated by noise or interference which can reduce the quality and clarity of sound caused by weather, being in crowded places and other factors. Therefore, noise reduction in voice signals is important in voice signal processing. This study aims to reduce noise in voice signals using the FFT method. The Fast Fourier Transform (FFT) method is used to identify frequencies and reduce noise in voice signals. The data used is in the form of recordings, namely the sound of speech and the sound of rain as noise. This research was conducted with the help of MATLAB R2022a software. The results of this study indicate that the FFT method is effective in reducing noise in the voice signal and improving the sound quality to be cleaner and clearer than the original sound signal before noise removal is performed.